EFFECT OF FINANCIAL PERFORMANCE AND GOOD CORPORATE GOVERNANCE ON VALUE OF COMPANY - Ratnasari, Diana; Chomsatu Samrotun, Yuli; Wijayanti, Anita (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2018)
This study aimsato Determine and analyzeathe influence of financialaperformance (returnson investment and return on equity) and good corporate governance (managerial ownership, independent board of commissioner, and the auditacommittee) to the value of the company. The population insthissstudysaresallsmanufacturingscompaniedslistedsonsthesIndonesia Stock Exchange period 2014 to 2016. Sampling technique in this study using purposive samplingsmethod, Obtained a sample of 19 companies over three periods, the resulting in a total sample of 57. Data analysis techniques used is using multiplearegressionaanalysis. The results of the feasibility study models (F test) shows that the variables return on investment, return on equity, managerial ownership, independent boardaofaCommissioners, andatheaauditacommittee influence the value of the company. The result of hypothesis test (t test) shows that the variable of return on investment, return on asset, and independent board of commissioner influence to firm value, while managerial ownership variable and audit committee have no effect to company value.